Effect of Acupuncture on the Motor and Nonmotor Symptoms in Parkinson's Disease—A Review of Clinical Studies - Zeng, Bai‐Yun (CNS Neurosci Ther, 2016)
Parkinson's disease is a neurodegenerative disorder. Parkinson's clinical feature is characterized by its motor manifestations, although its many nonmotor symptoms occur earlier and have more profound impact on the quality of patient's life. Acupuncture has been increasingly popular and has been used to treat patients with Parkinson's. In this article, we have studied the clinical reports of acupuncture treatment for Parkinson's, which were listed in Medline, PubMed, EMBASE, CNKI, and CINAHL databases in the past 15 years. It was found that acupuncture either manual or electroacupuncture stimulation at specific acupoints relieved some motor symptoms in patients with Parkinson's and markedly improved many nonmotor symptoms such as psychiatric disorders, sleep problems, and gastrointestinal symptoms. When it was used as an adjunct for levodopa, acupuncture improved therapeutic efficacy and reduced dosage and the occurrence of side effects of levodopa. However, the results were constrained by small sample sizes, methodological flaws, and blinding methods of studies. Although the evidence for the effectiveness of acupuncture for treating Parkinson's is inconclusive, therapeutic potential of acupuncture seems quite promising. More studies, either comparative effectiveness research or high‐quality placebo‐controlled clinical studies are warranted.